The effect of wine knowledge type on variety seeking behavior in wine purchasing. (3rd April 2018) - Ellis, Debbie; Mattison Thompson, Frauke
ABSTRACT: Wine is a prolific, but complex and information-intensive product, so it is important for marketers to understand the behaviors and characteristics of different wine market segments, in order to better target their marketing strategies to these different segments' needs. Yet little is known about how the characteristics of consumers' subjective and objective knowledge of wine impact their variety seeking purchasing behavior. As variety seeking behavior affects customer retention and loyalty, a better understanding of this behavior is important to wine marketers. Results of a survey show that wine knowledge types are a significant predictor of variety seeking purchasing behavior of wine. Wine consumers who think they know a lot about wine, tend to engage in more variety seeking behavior in their wine purchasing. This suggests that marketers should adapt their segmentation, targeting and channel strategies to individual knowledge types to be more successful.